Comparison of Prevalence and Outcomes of Pediatric Acute Respiratory Distress Syndrome Using Pediatric Acute Lung Injury Consensus Conference Criteria and Berlin Definition - Gupta, Samriti; Sankar, Jhuma; Lodha, Rakesh; Kabra, Sushil K. (Frontiers in Pediatrics, 2018)
Objectives Our objective was to compare the prevalence and outcomes of pediatric ARDS using the Pediatric Acute Lung Injury Consensus Conference (PALICC) criteria and Berlin definitions. Methods We screened case records of all children aged 1 month to 17 years of age admitted to the Pediatric Intensive Care Unit (PICU) over a 3 year period (2015- 2017) for presence of any respiratory difficulty at admission or during PICU stay. We applied both PALICC and Berlin criteria to these patients. Data collection included definition and outcome related variables. Data were compared between the 'PALICC only group' and the 'Berlin with or without PALICC' group using Stata 11. Results Of a total of 615 admissions, 246 were identified as having respiratory difficulty at admission or during PICU stay. A total of 61 children (prevalence 9.9%; 95% CI: 7.8 to 12.4) fulfilled the definition of ARDS with either of the two criteria. While 60 children (98%) fulfilled PARDS criteria, only 26 children (43%) fulfilled Berlin definition. There was moderate agreement between the two definitions (Kappa: 0.51; 95% CI: 0.40 to 0.62; observed agreement 85%). Greater proportion of patients had severe ARDS as per Oxygenation Index criteria in the 'Berlin with or without PALICC group' as compared to the 'PALICC only' group (36.3% vs. 17.2%). There was no difference between the groups with regard to key clinical outcomes such as duration of ventilation (7 vs. 8 days) or mortality [57.1% vs. 57.7%: RR (95% CI): 0.99 (0.64 to 1.5)]. Conclusion In comparison to Berlin definition, the PALICC criteria identified more number of patients with ARDS. Proportion with severe ARDS and complications was greater in the 'Berlin with or without PALICC' group as compared to the 'PALICC only' group. There were no differences in clinical outcomes between the groups. Key words: PARDS; Berlin definition; pediatric ARDS; Acute respiratory distress syndrome; Oxygenation index; oxygen saturation index